Development of Multimodal Animation–Based Digital Arabic Vocabulary Teaching Materials - Ahmad Afandi; Luthfi Anisatin; Very Aulia Rahman; Maghfiratun Maghfiratun (UIN Sunan Gunung Djati Bandung, 2025)
This study addresses the lack of structured, curriculum-aligned multimodal animation-based instructional media for Arabic vocabulary learning in Islamic higher education language programs. This study aimed to design animation-based Arabic vocabulary learning media using a multimodal learning approach. The research employed a research and development (R&D) method based on the ADDIE model. It was conducted up to the Analysis and Design stages at the Program Pengembangan Bahasa Arab (PPBA), Universitas Muhammadiyah Malang (UMM). Data were collected through classroom observations, student interviews, and the analysis of instructional materials to identify learners’ needs, material limitations, and media-related challenges in vocabulary learning. The results of the analysis indicated that vocabulary instruction was dominated by conventional, text-based methods, resulting in low learner engagement, limited vocabulary retention, and difficulties in contextual vocabulary use. Learning materials lacked multimodal support and a structured progression of difficulty, while instructional media showed minimal integration of visual and auditory elements. Based on these findings, an animation-based instructional design was developed, integrating visual illustrations, audio pronunciation, contextual example sentences, and formative assessment components. The study contributes theoretically by strengthening MALL (Mobile-Assisted Language Learning) design epistemology through multimodal animation alignment, and practically by offering a replicable, context-appropriate design model for Arabic vocabulary instruction in Islamic educational environments. The proposed framework establishes clear directions for development-stage validation, learner-agency balance, and interface signaling of skill-material alignment, ensuring accessibility for diverse learner profiles.